Organophosphorus Chemistry : Vol. 38 - Allen, D. W.; Tebby, J. C. (Cambridge : RSC pub,., 2009)
Annotation Coverage in this annual review of the literature presents a comprehensive survey of the vast field of study involving organophosphorus compounds, from phosphines and phosphonium salts through to phosphorous acids, nucleotides and ylides. The critical reviews in this volume enable industrial and academic researchers to keep abreast of the latest developments in their specialist fields.
Includes bibliographical references and index.
Keywords: Organophosphorus Chemistry